2006
DOI: 10.1161/01.atv.0000199519.37089.a0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Inhibition by Insulin Is Absent in Type 2 Diabetes Mellitus

Abstract: Objective-ADP-induced P2y 12 signaling is crucial for formation and stabilization of an arterial thrombus. We demonstrated recently in platelets from healthy subjects that insulin interferes with Ca 2ϩ increases induced by ADP-P2y 1 contact through blockade of the G-protein G i , and thereby with P2y 12 -mediated suppression of cAMP. Methods and Results-Here we show in patients with type 2 diabetes mellitus (DM2) that platelets have lost responsiveness to insulin leading to increased adhesion, aggregation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
148
2
5

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(159 citation statements)
references
References 53 publications
3
148
2
5
Order By: Relevance
“…6 Physiologically, insulin reduces platelet aggregation by inhibiting the P2Y 12 receptor, although this inhibition is absent in subjects with DM and insulin resistance. 32,33 In previous mechanistic studies, insulin-treated subjects had higher levels of platelet aggregation after dual antiplatelet therapy than subjects with DM not treated with insulin, indicating that treatment with insulin may identify a group of subjects at particular risk for poor response to clopidogrel. 22 We did not collect age of onset (juvenile versus adult) or duration of diabetes, both factors that may influence insulin use.…”
Section: Discussionmentioning
confidence: 97%
“…6 Physiologically, insulin reduces platelet aggregation by inhibiting the P2Y 12 receptor, although this inhibition is absent in subjects with DM and insulin resistance. 32,33 In previous mechanistic studies, insulin-treated subjects had higher levels of platelet aggregation after dual antiplatelet therapy than subjects with DM not treated with insulin, indicating that treatment with insulin may identify a group of subjects at particular risk for poor response to clopidogrel. 22 We did not collect age of onset (juvenile versus adult) or duration of diabetes, both factors that may influence insulin use.…”
Section: Discussionmentioning
confidence: 97%
“…There is accumulating evidence that platelet hyperactivity in patients with diabetes 32 is mediated by insulin resistance and increased P2Y12 signaling. 33 Other potential mechanisms include increased platelet turnover, altered platelet membrane structure, increased intracellular calcium, and abnormal glycation. 32,34,35 A recent study suggested that 150-mg daily maintenance dosage of clopidogrel resulted in greater platelet inhibition than conventional 75-mg daily dosing in patients with diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 Under laboratory conditions, type 2 diabetes platelets adhere better to a thrombogenic surface, form bigger aggregates at lower agonist concentration and produce more thromboxane A2 than do control platelets. 6 The hyperactivity correlates with loss of insulin sensitivity and intensive insulin treatment partly normalizes aggregation. 7 Inhibition of platelet responsiveness with aspirin therapy reduces the relative risk of myocardial infarction and stroke by about 10%.…”
Section: Introductionmentioning
confidence: 99%
“…Insulin also inhibits splicing of tissue factor pre-mRNA in platelets adhering to prothrombotic proteins and the loss of insulin responsiveness in type 2 diabetes might well contribute to the thrombogenicity of the platelet plug that forms upon plaque rupture. 6,11 Weight gain and appearance of insulin resistance go hand in hand and are thought to be caused by abnormal adipokine release by visceral fat. 12 Adipocytes release resistin, leptin, plasminogen activator inhibitor-1 (PAI-1), retinol binding protein 4 (RBP4) and visfatin and their plasma levels are elevated in individuals with abdominal obesity.…”
Section: Introductionmentioning
confidence: 99%